2018
DOI: 10.1093/ofid/ofy113
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the M184V Resistance Mutation on Virological Efficacy and Durability of Lamivudine-Based Dual Antiretroviral Regimens as Maintenance Therapy in Individuals With Suppressed HIV-1 RNA: A Cohort Study

Abstract: BackgroundDual therapy (DT) with boosted protease inhibitors (bPIs) plus lamivudine has been shown to be superior to bPI monotherapy in virologically suppressed patients despite previous selection of the lamivudine resistance M184V mutation. We compared the virological efficacy of lamivudine-based DT in patients with and without a history of M184V detection.MethodsWe retrospectively analyzed patients with HIV-RNA ≤50 copies/mL switching to DT with at least 1 previous resistance genotype in the ARCA database. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 18 publications
2
35
1
Order By: Relevance
“…As previously reported [5], the M184V mutation was not associated with VF. However, historical genotype could still be useful when deciding whether to simplify ART, as a consequence of the high risk of VF in patients with RAMs other than M184V.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…As previously reported [5], the M184V mutation was not associated with VF. However, historical genotype could still be useful when deciding whether to simplify ART, as a consequence of the high risk of VF in patients with RAMs other than M184V.…”
Section: Discussionsupporting
confidence: 84%
“…Despite their high efficacy, based on previous experience with nucleoside reverse transcriptase inhibitor (NRTI)-reducing strategies, some patients on two-drug regimens could be at higher risk of virological failure (VF); for instance, those with a shorter time of virological suppression [5]. Also, when considering simplification to NRTI-sparing regimens, a lower CD4 count nadir, longer antiretroviral (ARV) exposure, lower adherence and higher residual viraemia were also predictive of VF [6]: although this was not demonstrated in previous trials with two-drug regimens, it could still represent a concern in this group in the long term.…”
Section: Introductionmentioning
confidence: 99%
“…24 Our study also allows to frame the target of patients for whom this switch strategy may results more advantageous; in particular our data confirm that, even with a longer follow-up, the lone presence of the M184V resistance mutation is not a predictor of virological failure for this 3TC-containing dual regimen, probably because of the reduced replicative fitness caused to the virus by this mutation. [25][26][27] However, as previously reported by Gagliardini et al, 28 the M184V mutation appears to be associated with virological failure in patients with a reduced time of virological suppression at baseline. These results must bring to the attention of the clinician the need to collect a precise clinical and virological history of the patient before implementing a therapeutic simplification towards a two-drug regimen.…”
Section: Discussionmentioning
confidence: 58%
“…The elevated presence of M184V/I is expected and arises as a consequence of the use of 3TC as part of all the firstline regimens in China [23]. Although M184V/I causes high-level in vitro resistance to 3TC, M184V/I is not a contraindication to continued treatment with 3TC because it increases susceptibility to AZT, and in addition, it is associated with clinically significant reductions in HIV-1 replication [14,24,25]. Similar to our study finding, a high prevalence of M184 V/I mutation has been reported in Asia, Sub-Saharan Africa and Latin America, but a lower prevalence in western Europe [26][27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%